Feminism, Violence, and Representation in Modern Italy : "We are Witnesses, Not Victims" - Parmigiani, Giovanna (Book collections on Project MUSE., 2019)
"Can the way a word is used give legitimacy to a political movement? Feminism, Violence, and Representation in Modern Italy traces the use of the word "femminicidio" (or "femicide") as a tool to mobilize Italian feminists, particularly the Union of Women in Italy (UDI). Based on nearly two years of fieldwork among feminist activists, Giovanna Parmigiani takes a broad look at the many ways in which violence inflects the lives of women in Italy. From unchallenged gendered grammar rules to the representation of women as victims, Parmigiani examines the devaluing of women's contribution to their communities through the words and experiences of the women she interviews. She describes the first uses of the word "femminicidio" as a political term used by and within feminist circles and traces its spread to ultimate legitimization and national relevance. The word redefined women as a political subject by building an imagined community of potentially violated women. In doing so, it challenged Italians to consider the status of women in Italian society, and to make this status a matter of public debate. It also problematized the connection between women and tropes of women as objects of suffering and victimhood. Parmigiani considers this exchange within the context of Italian Catholic heritage, a precarious economy, and long-held notions of honor and shame. Parmigiani provides a careful and searing consideration of the ways in which representations of violence and the politics of this representation are shaping the future of women in Italy and beyond"--